Definição e delimitação dos circuitos de comercialização bovina como elemento metológico de intervenção sanitária: o caso da febre aftosa no estado de Mato Grosso do Sul - Geraldo Marcos de Moraes (1993)
The CCBs (Bovine trading circles) were developed to complement the understanding and practice in the agricultural region of the state of Mato Grosso do Sul, Brasil, 1989. The CCBs are defined as a geopolitical space constituted by elements which maintain a certain level of contact in terms of buying and selling and the movement of cattle of ingress and outlet of the state, over a fixed period. They where built by means of the analysis of cattle movement, which indicated the dynamism, intensity and predominance of entry and exit of animals in those municipal districts considered to be the primary unit of analysis. It was determined that the state of Mato Grosso do Sul presents three trade circles: the North-east, the North-west and the South plus 19 connection districts. The existing circuits points toward changes in the distribution of the cattle production systems of the state re ulting, mainly, from interiorezation of slaughter industries. It is concluded that the proposed methodology serves as dynamic instrument to strategic planning and that movement of animals, as a direct indicator, must be ,considered in the characterization of differentiated risk to transmissible diseases of acute nature, particularly foot-and-mouth disease.